1991
DOI: 10.1021/bi00101a009
|View full text |Cite
|
Sign up to set email alerts
|

Glycolysis and glucose uptake in intact outer segments isolated from bovine retinal rods

Abstract: Glucose transport across the plasma membrane of isolated bovine rod outer segments (ROS) was measured by uptake of 14C-labeled 3-O-methylglucose and 2-deoxyglucose and was inferred from deenergization of ROS with 2-deoxyglucose. Glucose transport was mediated by a facilitated diffusion glucose transporter that equilibrated external and internal free hexose concentrations. Glucose transport in ROS displayed two components as judged from kinetic analysis of hexose equilibration and as judged from inhibition by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Such a role for Glut1 was 3641 Glut1 in photoreceptors first proposed based on experimental evidence that glucose enters purified bovine rod outer segments in a process that can be inhibited by cytochalasin B and phloretin, both known antagonists of transport by the GLUT family of glucose transporters (Hsu and Molday, 1991;Lopez-Escalera et al, 1991). Immunohistochemical evidence of Glut1 in the outer segments from a variety of species has been offered by a number of laboratories in support of this model, but in all cases the resolution of the images did not allow outer segment plasma membranes to be distinguished from RPE microvilli (Elliott et al, 2008;Hsu and Molday, 1991;Mantych et al, 1993;Nihira et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a role for Glut1 was 3641 Glut1 in photoreceptors first proposed based on experimental evidence that glucose enters purified bovine rod outer segments in a process that can be inhibited by cytochalasin B and phloretin, both known antagonists of transport by the GLUT family of glucose transporters (Hsu and Molday, 1991;Lopez-Escalera et al, 1991). Immunohistochemical evidence of Glut1 in the outer segments from a variety of species has been offered by a number of laboratories in support of this model, but in all cases the resolution of the images did not allow outer segment plasma membranes to be distinguished from RPE microvilli (Elliott et al, 2008;Hsu and Molday, 1991;Mantych et al, 1993;Nihira et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The second role of Glut1 is to mediate glucose uptake by the photoreceptors themselves, because it is the only known glucose transporter expressed by these cells (Mantych et al, 1993). For nearly 20 years, Glut1 has been thought to localize in part to the plasma membrane of photoreceptor outer segments, on the basis of glucose transport activity measured in bovine rod outer segment preparations (Hsu and Molday, 1991;Lopez-Escalera et al, 1991) and immunohistochemical data published by a number of laboratories (Elliott et al, 2008;Hsu and Molday, 1991;Mantych et al, 1993;Nihira et al, 1995) (but see Kumagai et al, 1994). The presence of Glut1 on the outer segment plasma membrane has stood as an additional argument for local glucose utilization by the outer segment.…”
Section: Introductionmentioning
confidence: 99%
“…These observations were confirmed by western blotting of isolated rod OSs and measurements of glycolytic enzymes activities, as well as functional experiments with GLUT inhibitors of the uptake of a glucose analog (3‐ O ‐methylglucose). It was proposed that local glycolytic catabolism of glucose directly incorporated by the OS is one important source of ATP, although most likely not the only one; similar observations were done in bovine OSs [19]. A proteomics study of bovine rod OSs reported the presence of GLUT1 [61], although this protein was not among those detected in another proteomics study [62].…”
Section: Atp Sources For Sperm Flagella and Ciliamentioning
confidence: 93%
“…By which mechanism could retinal photoreceptors not only survive, but thrive in the absence of Gpi1, an extremely ancient enzyme known as ubiquitous amongst living cells? Glycolysis certainly does take place in retinal photoreceptors (Hsu & Molday, 1991,1994; Lopez‐Escalera et al ., 1991). Bovine rod outer segments (ROS) contain not only GLUT‐1 glucose transport activity, but also activities for the glycolytic enzymes hexokinase, phosphofructokinase‐1, aldolase, glyceraldehyde‐3‐phosphate dehydrogenase, phosphoglycerate kinase, as well as lactate dehydrogenase (Hsu & Molday, 1991).…”
Section: Discussionmentioning
confidence: 99%